2007
DOI: 10.1007/s00467-006-0328-7
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide toxicity in cultured proximal renal tubule cells

Abstract: Renal injury is a common side effect of the chemotherapeutic agent ifosfamide. Current evidence suggests that ifosfamide metabolites, particularly chloroacetaldehyde, produced within the kidney contribute to nephrotoxicity. The present study examined the effects of ifosfamide and its metabolites, chloroacetaldehyde and acrolein, on rabbit proximal renal tubule cells in primary culture, using a transwell culture system that allows separate access to apical and basolateral cell surfaces. The ability of the uropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
(40 reference statements)
3
9
0
Order By: Relevance
“…This is why, in our study, the long-term toxicity of very low concentrations of CAA was studied in precision-cut cortical slices. In the sham group, our observation that the 24-h incubation of kidney slices with low concentration of CAA led to significant decreases in cellular levels of ATP, total glutathione and coenzyme A + acetyl-coenzyme A is in accord with previously published studies in cultured cells [30,32,33,42,43]. In contrast to in vitro addition, in vivo mesna or amifostine administration did not prevent CAA toxicity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is why, in our study, the long-term toxicity of very low concentrations of CAA was studied in precision-cut cortical slices. In the sham group, our observation that the 24-h incubation of kidney slices with low concentration of CAA led to significant decreases in cellular levels of ATP, total glutathione and coenzyme A + acetyl-coenzyme A is in accord with previously published studies in cultured cells [30,32,33,42,43]. In contrast to in vitro addition, in vivo mesna or amifostine administration did not prevent CAA toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…We also demonstrated that the nephrotoxic effects of 0.5 mM CAA were prevented by addition to the incubation medium of an equimolar concentration of mesna or a tenfold higher concentration of amifostine [12]. These results were confirmed by several studies conducted by other authors, showing that mesna and amifostine could prevent toxicity of CAA in vitro [30][31][32][33]. Despite the fact that the protecting concentration of thiols compounds were quite different among the various studies (from 200 to 800 ÎŒM), it must be emphasised that the protecting effect obtained under in vitro conditions was very efficacious and was promising to also prevent CAA toxicity in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…Here we demonstrate an alternative to wholegenome amplification, in which we have cultured single fibroblasts briefly as clonal isolates for a few generations to extract enough genomic DNA to complete multiple PCR genotyping reactions. Many types of cells, including hepatocytes (Tateno and Yoshizato 1999), adipocytes (Sugihara et al 1987), astrocytes (Mbarek et al 1998), renal tubular cells (Springate and Taub 2007), and epithelial cells from colon (Follmann et al 2000), prostate (McKeehan et al 1984), and mammary glands (Soule and McGrath 1986) can grow in primary cell culture, if not immortally, then for at least a few generations. And for those cell types that may be terminally differentiated or otherwise incapable of reentry into the cell cycle, another possibility involves expression of a conditionally immortalizing gene from a DNA tumor virus, such as the SV40 T-antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Woodland et al [14] then hypothesized that local renal metabolism of IFO to CAA -not systemic exposure -produces renal tubular damage. Although other toxic species such as acrolein are produced from IFO, metabolism studies by Springate and Taub [34] have demonstrated CAA to be the main nephrotoxic IFO metabolite.…”
Section: Caamentioning
confidence: 98%